Efektifitas Latihan Berbasis Virtual Reality terhadap Kemampuan Pengambilan Keputusan Taktis Pemain Futsal: Studi Quasi- Eksperimental - Andri Arif Kustiawan; Pomo Warih Adi; Agus Pribadi; Bimo Alexander; Zulham (MAN Insan Cendekia Jambi, 2026)
Tactical decision-making is a fundamental component influencing futsal players' performance in responding to rapidly changing game situations. However, conventional training methods have limitations in providing representative game simulations, highlighting the need for innovative approaches through Virtual Reality (VR) technology. This study aimed to examine the effectiveness of Virtual Reality-based training on the tactical decision-making ability of members of the Student Sports Club (UKM Bola) at Universitas PGRI Yogyakarta. This study employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The participants consisted of 30 students selected through purposive sampling and assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received Virtual Reality-based training for eight weeks, while the control group participated in conventional futsal training. Tactical decision-making ability was assessed using the Game Performance Assessment Instrument (GPAI). Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene's homogeneity test, paired-sample t-test, independent-sample t-test, and Cohen's d effect size with a significance level of 0.05. The findings revealed that the experimental group demonstrated greater improvement in tactical decision-making ability than the control group. Hypothesis testing indicated a significant difference between the two groups after the intervention (p < 0.05), with a very large effect size. These findings indicate that Virtual Reality-based training is more effective than conventional training in improving tactical decision-making ability among futsal players. Therefore, Virtual Reality can be considered an innovative technology-based training method to support futsal coaching programs in higher education.